Multiple-parallel-concatenated single-parity-check (MPCSPC) codes for magnetic recording systems - Low, Kang Cai. (2010)
In this project, we consider a low-complexity coding scheme that is constructed by concatenating in parallel multiple branches of single-parity-check (SPC) codes. The code, which is termed as multiple-parallel-concatenated single-parity-check (MPCSPC) codes, possesses many desirable properties for magnetic recording systems including sufficient flexibility to achieve very high code rates and various block lengths. The MPCSPC code has an encoder structure similar to that of classical parallel-concatenated turbo codes. Decoding is achieved by viewing the code as a special type of irregular low-density parity-check (LDPC) codes and applying the sum-product algorithm (SPA) to the code graph in a serialized branch-by-branch fashion.